Growth and yield respons of mungbean to different level of organic and inorganic fertilizer in North Sumatera - Siti Fatimah Batubara (Agrotech Journal, 2022)
Integrated nutrient management is an alternative for the sustainable and cost-effective management of soil fertility by combined apply of organic with inorganic fertilizer resulting in rising soil fertility and productivity. This study aims (i) to determine the growth and yield respons of mungbean to different level of organic and inorganic fertilizer, and (ii) to measuring the effectiveness of organic fertilizer on mungbean production. The research was conducted at Pasar VI Kwala Mencirim Village, Sei Bingai District, Langkat Regency, North Sumatra in December 2020 to April 2021. This study used a Non-Factorial Randomize Complete Block design consisting of seven treatments and four replications, namely P0 (without fertilizer), P1 (100% dose of NPK fertilizer), P2 (75% dose of NPK fertilizer), P3 (50% dose of organic fertilizer + 75% NPK fertilizer) P4 (100% dose of organic fertilizer + 75% NPK fertilizer), P5 (150% dose of organic fertilizer + 75% NPK fertilizer), and P6 (1 dose of organic fertilizer + 100% NPK fertilizer). Plant height observations were carried out at 4, 6, and 8 weeks after planting and production observations were at harvest. Analysis of varian (ANOVA) was used to determined the effect of fertilizers treatment and followed by Duncan Multiple Range Test (DMRT) at 5% confidence interval for significant differences between treatment on plant growth and production. Organic fertilizer effectiveness was calculating using the Relative Agronomy Effectiveness (RAE). The results showed that organic fertilizer had a significant effect on mungbean growth and yield compared to controls. The highest mungbean production in P6 treatment of 1209 Kg/ha while the control treatment was 512 Kg/ha. Organic fertilizer was effective to increase mungbean production. The highest relative agronomic efficiency (RAE) was 438% in the treatment of organic fertilizer fertilizer at P6 of 100% dose of organic fertilizer +100% NPK fertilizer